2007
DOI: 10.1007/s11745-007-3022-z
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiles of Genes Involved in Fatty Acid and Triacylglycerol Synthesis in Castor Bean (Ricinus communis L.)

Abstract: Castor seed triacylglycerols (TAGs) contain 90% ricinoleate (12-hydroxy-oleate) which has numerous industrial applications. Due to the presence of the toxin ricin and potent allergenic 2S albumins in the seed, it is desirable to produce ricinoleate from temperate oilseeds. To identify regulatory genes or genes for enzymes that may up-regulate multiple activities or entire pathways leading to the ricinoleate and TAG synthesis, we have analyzed expression profiles of 12 castor genes involved in fatty acid and TA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
44
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 32 publications
10
44
0
1
Order By: Relevance
“…3). The results, especially the expression patterns of DGAT and PDAT during peanut pod development, are quite consistent with the previous study (Chen et al 2007;Li et al 2010). These results indicated that peanut pod first accumulate high levels of the enzymes for the oil biosynthesis in the early stage of peanut pod development before the latter stage (15 DASP), when high rates of the oil biosynthesis might be obtained.…”
Section: Discussionsupporting
confidence: 91%
“…3). The results, especially the expression patterns of DGAT and PDAT during peanut pod development, are quite consistent with the previous study (Chen et al 2007;Li et al 2010). These results indicated that peanut pod first accumulate high levels of the enzymes for the oil biosynthesis in the early stage of peanut pod development before the latter stage (15 DASP), when high rates of the oil biosynthesis might be obtained.…”
Section: Discussionsupporting
confidence: 91%
“…Quantitative expression data of each gene were subjected to gene expression clustering analysis using the k-mean clustering method [26,27] provided within the software expression analyzer and display (EXPANDER) [28]. Input data were first standardized using mean = 0 and variance = 1, and fixed norm and then pursued clustering with k-mean method.…”
Section: Gene Clustering and Visualizationmentioning
confidence: 99%
“…About 90% of the seed TAGs is composed of ricinoleic acid (12-hydroxy-oleate), which is unusual hydroxylated fatty acid highly valued for chemical and pharmacological application [2]. It has been proposed that castor bean has a potential to produce biodiesel, because of its unique properties that the seed has high oil content, toxic storage protein (ricin) confers oil source without competition to food resource and the plant can tolerate to severe environments where food crops are unfavorable [3].…”
Section: Introductionmentioning
confidence: 99%